2017
DOI: 10.1111/1744-7917.12543
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional analysis of hsp18.3 gene in the red flour beetle, Tribolium castaneum

Abstract: Small heat shock proteins (sHSPs) are diverse and mainly function as molecular chaperones to protect organisms and cells from various stresses. In this study, hsp18.3, one Tribolium castaneum species-specific shsp, has been identified. Quantitative real-time polymerase chain reaction illustrated that Tchsp18.3 is expressed in all developmental stages, and is highly expressed at early pupal and late adult stages, while it is highly expressed in ovary and fat body at the adult period. Moreover, it was up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…As T. castaneum is basically living in the warm cereal storage place and without diapause, Tchsp21.8b was in response to heat but exhibited insensitiveness to cold stress. This phenotype was also existed in ER‐based Tchsp90 and Tchsp18.3 , both of which were only upregulated by heat stress (Xie et al., ; Zhang, Gu et al., ), indicating that the behaviour would make a similar induction of other hsps in T. castaneum .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As T. castaneum is basically living in the warm cereal storage place and without diapause, Tchsp21.8b was in response to heat but exhibited insensitiveness to cold stress. This phenotype was also existed in ER‐based Tchsp90 and Tchsp18.3 , both of which were only upregulated by heat stress (Xie et al., ; Zhang, Gu et al., ), indicating that the behaviour would make a similar induction of other hsps in T. castaneum .…”
Section: Discussionmentioning
confidence: 92%
“…Particularly, although some of the orthologous shsps could be upregulated or inhibited under the different stresses, their responses are negligible compared to the species‐specific shsps and the members of hsp70 and hsp90 family. Suffering the extreme temperature stimulation, many species‐specific shsps can be induced hundreds or even thousands folds, such as Tchsp18.3 , Pxhsp20.09 , Cshsp21.7b and so on (Chen & Zhang, ; Lu et al., ; Xie et al., ). Likewise, Tchsp18.3 , Tchsp68 and Tchsp83 mRNA levels significantly increased during the first 2 hr of UV exposure and the highest upregulation could reach to 8.90‐fold (Sang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that heat shock protein genes affect insect reproduction and longevity. Xie et al (2019) studied the functional of hsp18.3 gene in the Tribolium castaneum and found that after injection of dshsp18.3, one pair of the beetles can hardly spawn. When Tchsp18.3 was knocked down, the survival rate of adults and fecundity were significantly lower than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a total of 200 ng of the dsRNA in 200 nL solution was injected into the body cavity of each larva (∼15 days old). Injection of an equal volume of physiological buffer only (IB) and non‐injection (wild‐type, WT) were served as negative controls . Three biological replications with independent injections were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Injection of an equal volume of physiological buffer only (IB) and non-injection (wild-type, WT) were served as negative controls. 46,54 Three biological replications with independent injections were conducted. Additionally, to confirm that the results we observed in the subsequent RNAi analysis were due to suppression of the expression levels of the specific target genes and not to the presence of dsRNAs, we also injected GFP dsRNA in an equal volume of IB into 15-day-old T. castaneum larvae.…”
Section: Double-stranded Rna Synthesis and Injectionmentioning
confidence: 99%